Adverse drug reactions and urological disease. Issue 3 (May 2017) - Badyal, Karamjit; Anton, Christopher; Ferner, Robin
Abstract : Despite the significant benefits of today's drugs, they still have the potential to cause significant adverse effects. Here the authors briefly review urological disorders caused by drugs and adverse reactions caused by drugs used to treat urological disorders.